Bacterial Shape and ActA Distribution Affect Initiation of Listeria monocytogenes Actin-Based Motility - Rafelski, Susanne M. (Biophysical Society, 2005)
We have examined the process by which the intracellular bacterial pathogen Listeria monocytogenes initiates actin-based motility and determined the contribution of the variable surface distribution of the ActA protein to initiation and steady-state movement. To directly correlate ActA distributions to actin dynamics and motility of live bacteria, ActA was fused to a monomeric red fluorescent protein (mRFP1). Actin comet tail formation and steady-state bacterial movement rates both depended on ActA distribution, which in turn was tightly coupled to the bacterial cell cycle. Motility initiation was found to be a highly complex, multistep process for bacteria, in contrast to the simple symmetry breaking previously observed for ActA-coated spherical beads. F-actin initially accumulated along the sides of the bacterium and then slowly migrated to the bacterial pole expressing the highest density of ActA as a tail formed. Early movement was highly unstable with extreme changes in speed and frequent stops. Over time, saltatory motility and sensitivity to the immediate environment decreased as bacterial movement became robust at a constant steady-state speed.